Etični vidiki vrhunskega športa mladih - Zurc, Joca (Šport (Ljubljana), 2018)
The phenomenon of the elite achievements raises a questions of its visibility and specific approaches of their creations at any area of the human activity. These features come to the foreground even stronger when the elite achievements are created by children and youth. At one side, the society is responsible to develop the full potential of individual athlete, and at the same time is crucial to protect athlete%s right, dignity and health. The aim of our review study was to get insight into the ethical aspects, dilemmas and conceptual innovations of development young talented athletes. Three different literature review approaches by Grant and Booth (2009) were used. The study findings highlighted the three main conceptual approaches for addressing the ethical perspectives of the elite youth sport: 1) factors and risks of the young athletes% development, 2) defining ethics within the elite youth sport, and 3) implementation of the young athletes% basic rights and dignity. The establishment of the standardised approaches are necessarily to ensure the wellbeing of young top athletes and to reduce a pressure of the early specialisation in sport.
Keywords: dejavniki tveganja; nadarjenost; šport; športna etika; vrhunski šport; zdravje